(3OQGSGJ GdLOhi GdEbJUGOjI hJbjje CUhd GdeTQhYGJ (B/s - (3YHO GdQMje, eMeO GHQGgjes ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2007)
(3jVe CgejI OQGSGJ GdLOhi, OQGSGJ GdLOhi GdJaUjdjI, GdOQGSGJ GdShbjI, LOhi dfehPL GdJLGQj, GdOQGSI GdafjI, LOhi GSJQGJjLjI GdJNGQL, GMJSGH UGaj GdbjeI GdMGdjI heYOd GdYGFO GdOGNdj HhGSWI GdMGSH GdBdj, GdJMdjd GdeGdj HGSJNOGe GdfSH GdeGdjI, GdJMdjd GdeGdj HGSJNOGe GdMGSH GdGdj, GSJNOGe GdJMdjd GdeGdj aj GdJfHD HGdaTd GdeGdj, JSYjQ hJbjje GdTQcGJ, Jbjje GdGUhd ZjQ GdedehSI, feGPL hMGdGJ JWHjbjIs
(3HHdjhZQGajG(B: (3U(B308-312s
Keywords: (3GdeTQhYGJ(B-(3JUajIs; (3GdeTQhYGJ(B-(3Jehjds